Designing multifunctional forest systems in Northern Patagonia, Argentina - Garibaldi, Lucas Alejandro; Zermoglio, Paula F.; Agüero, Juan I.; Nacif, Marcos E.; Goldenberg, Matias Guillermo; Fioroni, Facundo; Amoroso, Mariano Martin; Aparicio, Alejandro Gabriel; Dimarco, Romina Daniela; Fernandez, Margarita; Fernandez, Natalia Veronica; Gambino, Micaela; et al. (Frontiers Media, 2025)
Multifunctional productive systems based on native species management, a new paradigm that counters colonial worldviews, offer sustainable sources of food and materials while preserving biodiversity. Despite extensive discussions in herbaceous and agricultural systems, applying this concept to native forests in Northern Patagonia remains unclear. Multifunctional system implementation can be approached from a fractal perspective, with evaluations at the stand level being essential for understanding ecological processes across scales. Here, we exemplify research and management for multiple native species, integrating results from 10 years of field experiments on the impacts of biomass harvesting intensity (HI) on nine Nature's Contributions to People (NCPs), including habitat creation, pollination, soil formation, hazard regulation, prevention of invasions, and provision of energy, food, materials, and options. Our findings reveal that some regulating NCPs peak with null HI, while certain material and regulating NCPs maximize at the highest HI. Low to intermediate HI (30–50%) show a more balanced provision of all NCPs. Our results suggest that some biomass extraction is necessary to enhance most NCPs, emphasizing the importance of balancing material provisioning and biodiversity conservation in management schemes. We propose future directions for designing multifunctional forest systems, advocating for low-density plantation of native tree species with high wood quality within the natural forest matrix. This approach may yield higher NCPs levels over time compared to the current cattle breeding and wood extraction system, with implications beyond Patagonia, considering historical associations of such practices with colonial worldviews globally.